2015
DOI: 10.1037/lat0000037
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapting parent training for Latino youth with ADHD: Development and pilot.

Abstract: Focus group data from Latino parents, research examining Latino cultural values, and recommendations from mental health providers working with Latino families were used to culturally adapt, an evidence-based parent training program for Latino youth with attention-deficit/hyperactivity disorder (ADHD). Session-specific, cultural adaptations were made to 5 sessions, and 2 sessions were completely replaced with newly developed, more culturally congruent sessions. The adapted treatment also resulted in global adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Similarly, a trend also indicated that parents reported less hyperactivity/impulsivity following CAT relative to baseline. Importantly, these findings are even more robust than those reported for the initial pilot of CAT (n = 5; Gerdes et al, 2015).…”
Section: Adhd Symptomatology and Functioning Outcomessupporting
confidence: 50%
“…Similarly, a trend also indicated that parents reported less hyperactivity/impulsivity following CAT relative to baseline. Importantly, these findings are even more robust than those reported for the initial pilot of CAT (n = 5; Gerdes et al, 2015).…”
Section: Adhd Symptomatology and Functioning Outcomessupporting
confidence: 50%
“…According to meta-analytic data, positive outcomes are associated with exposure to PT interventions, such as improvements in parent-child relationships, nonpunitive parenting, and successful child and youth development (Michelson et al, 2013). However, there are a limited number of studies focused on empirically testing culturally adapted PT interventions for underserved Latino/a immigrant families with adolescents (Allen et al, 2013; Estrada et al, 2017), and particularly scarce when referring to Mexican-origin families (Gerdes et al, 2015). Addressing this gap in research is necessary when considering the mental health disparities that negatively impact Latino/a immigrants in the US (Alegria, Atkins, Farmer, Slaton, & Stelk, 2010; Johnston, O’Malley, Bachman, Schulenberg, & Miech, 2016; Park et al, 2017).…”
Section: Scope Of the Studymentioning
confidence: 99%
“…An increasing body of evidence also indicates the positive effects of PT interventions on youth internalizing problems (Perrino et al, 2014). However, the availability of efficacious culturally adapted PT prevention interventions for low-income Latino/a families with adolescents continues to be scarce (Gerdes, Kapke, Lawton, Grace, & Hurtado, 2015; Gonzales et al, 2012). …”
mentioning
confidence: 99%
“…To address this need, DSM-5 introduced a CFI that streamlined the process of data collection for the OCF. 49 Another approach to navigating care within the minority population is the CCM. The term culture refers to the values, knowledge, and practices that an individual derives from being a member of diverse social groups; it incorporates aspects of an individual's background, development, and experiences; and takes into account an individual's perspective and that of family, friends, and community members, which may influence the patient's illness experience.…”
Section: Interventionsmentioning
confidence: 99%